SURVEY STUDY FOR VEHICULAR AD HOC NETWORKS PERFORMANCE IN CITY AND URBAN RESIDENTIAL AREAS - Eissa, Adel (My University, 2017)
This thesis it survey study for VANET (Vehicular Ad-Hoc Networks) and it performance in city and urban residential areas, when the the number of vehicles on roads is increasing annually, due to the higher amount of traffic, there are more accidents associated with road traffic complexity. VANET can be used to detect dangerous situations which are forwarded to the driver assistant system by monitoring the traffic status.
Keywords: VANET; wireless communications; mobility modelling; traffic safety.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|